HUBUNGAN ANTARA MOTIF DAN KEPUASAN PENONTONDALAM MENONTON YOUTUBE: Studi Korelasi Motif dan Kepuasan Penonton dalam Menonton Tonight Show di YouTube Pada Mahasiswa Ilmu Komunikasi di Surakarta - Ayu Sinaga, El Grace; Maya Sekar Wangi; Siswanta (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
Tonight Show is a very popular talk show program on television and also has an official channel on YouTube. Its presence on YouTube offers accessibility to reach a global audience. Therefore, understanding the motives and satisfaction of the audience is important. This research aims to determine the relationship between motives and audience satisfaction in watching YouTube. The theory used to analyze this research is the uses and gratification theory. This research is quantitative research with data collection using a questionnaire distributed to respondents. The population in this research were communication science students in Surakarta, totaling 3,248 students with a research sample of 100 students. This research uses a random sampling method to take samples. The hypothesis in this study was tested using the Spearman correlation test. The research results state that there is a positive and significant relationship between motives and satisfaction in watching the Tonight Show on YouTube. This is indicated by the correlation coefficient value of 0.864. In the Spearman rank interpretation, this value means that there is a very strong relationship with motives and satisfaction in watching YouTube.